Hemispheric Asymmetry on the Electroencephalogram during General Anesthesia Responsive to Blood Pressure Manipulations - Bryan T. Nycz; Andrew Chalhoub; Gaurav P. Patel; Cassandra E. Dean; Alexander Papangelou (Neurology International, 2022)
The electroencephalogram (EEG) has been extensively used to detect ischemia and the need for shunting during carotid endarterectomy. Limited literature exists using EEG data to detect ischemia in other surgeries. This case report depicts a 65-year-old man, with extensive vascular history including complete left carotid occlusion and severe right carotid stenosis, who presented for left first rib resection and left subclavian vein balloon angioplasty. Following induction of general anesthesia, frontal EEG (SedLine; Masimo Corporation, Irvine, CA, USA) demonstrated hemispheric asymmetry, which nearly resolved with vasoactive support. At three distinct periods, discordance reoccurred necessitating a higher mean arterial pressure threshold. This case demonstrates EEG patterns concerning for focal spectrographic ischemia and highlights the potential use of EEG signals to capture hypoperfusion and direct vasoactive therapy.